Output Based Learning (OutBaL): A Complete Research Learning for Health Student - Heru Santoso Wahito Nugroho; Edmelyn B. Cacayan; Angelito E. Alvarado; Wiwin Martiningsih; Joel Rey U. Acob; Kasad Kasad (Aloha International Journal of Health Advancement (AIJHA), 2024)
Output Based Learning (OutBaL): A Complete Research Learning is structured as a complete innovative approach to research learning, which does not only end up with research reports, but continues until the realization of research outputs in the form of scientific publications, such as journal articles, proceedings or monograph books are realized. With the publication of student research findings, the innovations found can be used directly by the community, both for application and further research. Complete learning to output like this is also expected to have a big positive impact on the development of higher education, both in terms of student and lecturer performance. Keywords: output based learning; complete research learning